PENGAWASAN PENERBITAN PASPOR DALAM RANGKA PENCEGAHAN TKI NONPROSEDURAL DI KANTOR IMIGRASI KELAS I PADANG - Lyzia Permata Mardizan; Syamsir Syamsir (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
This study aimed to determine the supervision carried out by the Office of Immigration Class I Padang in an effort to prevent the emergence of non-procedural labor migrants.The method used in this research is qualitative descriptive. The techniques used for data collection in this study are interviews, field observations, and study of documents and literature. This research was conducted at Class I Immigration Office Padang. The informants in this study were selected using purposive sampling technique. Test the validity of the data using Source triangulation techniques. Data analysis techniques were carried out by reducing data, displaying data, and drawing conclusions during the study. The results of the field research indicate that the supervision carried out by Padang Class I Immigration Office in its efforts to prevent the emergence of Non-procedural Migrant Workers in its implementation has run quite well, but there are still obstacles such as many passport applicants who do not provide information when they will work abroad, therefore it is necessary to increase supervision in each service process, especially during the interview process by the Padang Class I Immigration office so that the passport issued can be used according to its function.